Aging-associated prostate smooth muscle hypercontractility in rats - Tabatha Danielle da Silva Lopes; Renan Bazuco Fritoli; Fabio Henrique da Silva; Fabiano Beraldi Calmasini (Universidade de São Paulo, 2023)
Abstract Benign prostatic hyperplasia (BPH) is a multifactorial disease, highly associated with aging and characterized by increased prostate smooth muscle (PSM) contractility. Animal models have been employed to explore the aging-associated PSM hypercontractility; however, studies have focused in old animals, neglecting the initial alterations in early ages. The determination of prostatic dysfunctions onset is crucial to understand the BPH pathophysiology and to propose new BPH treatments. Considering that PSM contractility in 10-month-old rats has already been explored, the aim of the present study was to characterize the PSM contractility in younger rats. Male Wistar control (3.5-month-old), 6- and 8-month-old rats were used. Concentration-response curves to phenylephrine and electrical-field stimulation (EFS) were conducted in prostate from all groups. For the first time, we showed that 6- and 8-month-old rats exhibit PSM hypercontractility. The increased prostate contractility to phenylephrine starts around at 6-month-old, worsening during the aging. The 8-month-old rats exhibited hypercontractility to phenylephrine and EFS compared to the control and 6-month-old groups. Reduced phenylephrine potency was observed in 8-month-old rats, indicating an increased age-dependent prostate sensibility to this agonist. Collectively, our findings support the use of 6- and 8-month-old aged rats as new models to explore prostate hypercontractility in BPH.